2002
DOI: 10.1067/mtc.2002.124387
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pericardial effusion after orthotopic heart transplantation

Abstract: Postoperative pericardial effusions develop in approximately 20% of patients undergoing orthotopic cardiac transplantation. On the basis of the risk factors identified in this study, prevention may prove difficult, although avoidance of the intraoperative use of aminocaproic acid may be helpful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 13 publications
0
31
0
5
Order By: Relevance
“…It cannot be explained on the same principle as the formation of lymphoceles post-renal transplantation, which occurs in the non-absorptive retroperitoneal space. After cardiac transplant surgeries, an incidence of 21% moderate to large pericardial effusion (18) and 6% pleural effusion (19) have been reported in the absence of immunosuppression with sirolimus. The pericardial effusion may be explained by post-operative bleeding, however, an imbalance in the production and absorption of the secretion by the epithelial lining of the pleural…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be explained on the same principle as the formation of lymphoceles post-renal transplantation, which occurs in the non-absorptive retroperitoneal space. After cardiac transplant surgeries, an incidence of 21% moderate to large pericardial effusion (18) and 6% pleural effusion (19) have been reported in the absence of immunosuppression with sirolimus. The pericardial effusion may be explained by post-operative bleeding, however, an imbalance in the production and absorption of the secretion by the epithelial lining of the pleural…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial effusion is a frequent occurrence after heart transplantation, with moderately to large effusions reported in approximately a fifth of recipients (73,(75)(76)(77). Mortality and hospital stay are unaffected (75)(76)(77), although one study suggested an association between pericardial effusions and acute rejection (78).…”
Section: Pericardial and Pleural Effusionsmentioning
confidence: 99%
“…Mortality and hospital stay are unaffected (75)(76)(77), although one study suggested an association between pericardial effusions and acute rejection (78).…”
Section: Pericardial and Pleural Effusionsmentioning
confidence: 99%
“…Subsequent clot lysis may encourage fluid inspissation, leading to an effusion. However, it is noteworthy that the amount of mediastinal chest drainage, duration of chest tube drainage, and the quantities of blood products administered after transplantation were not found to correlate with the development of pericardial effusions (12). So, the underlying basis for CP in the posttransplant setting is most likely the accumulation of blood products within the pericardial sac with subsequent deposition and healing of the pericardial surface.…”
Section: Discussionmentioning
confidence: 97%
“…Antifibrinolytic agents, such as aminocaproic acid, can be used in the perioperative setting to reduce postoperative bleeding. This agent was found to be associated with a dramatically increased incidence of postoperative pericardial effusion and may contribute to retention of clots within the pericardial sac (10,12). Subsequent clot lysis may encourage fluid inspissation, leading to an effusion.…”
Section: Discussionmentioning
confidence: 99%